2015
DOI: 10.1007/s10620-015-3823-5
|View full text |Cite
|
Sign up to set email alerts
|

Serum 25-Hydroxyvitamin D Levels and the Risk of Dysplasia and Esophageal Adenocarcinoma in Patients with Barrett’s Esophagus

Abstract: Serum 25(OH)D levels were low in 58.3 % of our BE cohort. There was no association between 25(OH)D levels and prevalence or incidence of HGD/EAC in patients with BE. Further long-term studies are needed to study the association between vitamin D status and progression of dysplasia in BE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…In patients with Barrett's esophagus, no association was found between circulating 25(OH)D levels and incidence of esophageal adenocarcinoma despite a high prevalence of vitamin D deficiency (23.6%) or insufficiency (34.7%) 81 . However, in another study, patients receiving vitamin D supplements postoperatively for esophageal cancer had a longer disease‐free period, although there was no difference in overall survival 82 …”
Section: Vitamin Dmentioning
confidence: 99%
“…In patients with Barrett's esophagus, no association was found between circulating 25(OH)D levels and incidence of esophageal adenocarcinoma despite a high prevalence of vitamin D deficiency (23.6%) or insufficiency (34.7%) 81 . However, in another study, patients receiving vitamin D supplements postoperatively for esophageal cancer had a longer disease‐free period, although there was no difference in overall survival 82 …”
Section: Vitamin Dmentioning
confidence: 99%
“…Finally, a BE registry cohort study found no association between circulating 25(OH)D concentration and risk of prevalent or incident dysplasia or EAC in BE patients (36). The findings from the present Mendelian randomization study provide further evidence that 25(OH)D concentration is not associated with the risk of BE or EAC.…”
Section: Discussionmentioning
confidence: 40%
“…Conversely, a case-control study in Australia reported a decreased risk of EAC with higher ultraviolet B exposure although, even if a true finding, this is not necessarily due to vitamin D (9). While there is some evidence that BE patients are often vitamin D insufficient (35,36), studies to date have found no association between vitamin D intake and the risk of BE (10), and vitamin D supplementation has been shown to have no effect on risk of neoplastic progression in BE patients (35).…”
Section: Discussionmentioning
confidence: 98%
“…These results are similar to recent findings by Thota et al reporting a mean 25-OH vitamin D level of 72 nmol/L (29 ng/mL) in a registry of 429 BE patients. [ 47 ] In that study, there was no association between vitamin D status and incidence or prevalence of HGD/EAC. An older prospective study demonstrated an association between low vitamin D levels and increased risk for esophageal cancer, not further delineated by histologic subtype.…”
Section: Discussionmentioning
confidence: 77%